Principal Leadership Contribution and Teacher Competence in Improving Teacher Performance - Indajang, Kevin; Sherly, Sherly; Halim, Fitria (Journal of Education Reseach and Evaluation, 2021)
Optimizing the performance of a teacher is very important to support a quality learning process. To support the improvement of a teacher's performance, a crucial role in the leadership style of the principal, and the competence of teachers in a comprehensive manner is needed. This study aims to analyze the effect of principal leadership and teacher competence on teacher performance. This research uses a quantitative approach to causality. Data were collected through documentation and questionnaires. This study used a sample of 98 respondents with the determination of the sample size using the saturated sample formula. A partial least square is applied to examine the relationship between teacher performance, principal leadership, and teacher competence. The results of this study indicate that the principal's leadership variable has a significant contribution to improving teacher performance. Furthermore, the competencies possessed by a teacher also have a significant contribution to improving teacher performance.